The impact of material and moral factors in encouraging the local citizen participation - DEHBI , Wahiba (Journal of Social Sciences and Humanities, 2021)
Our research investigates the citizen participation issueat the local sphere, its role and effectiveness in enabling the individual to participate in the main public intervention projects, including the realization of development, according to the means available as well as the social variables of the local community. We focused on this subject to identify the main factors and influences that motivate individuals to participate in order to develop the local area in which they belong on the one hand. On the other hand, we have attempted to investigate the social elements of the local community around the concept of participatory work. From these indicators, we will review in our research, while emphasizing the importance of investing in local capacity and encouraging local solidarity of citizens through their participation in this process. On this basis, we have conducted a study to determine the main influences that drive individuals to take the initiative and allowing them to change and improve the local community, based on the qualitative approach by using the interview technique among eleven participants residing in the 26 building where the project was conducted ( RabiaTaherdistrict, Bab Ezzouar municipality), the study resulted that participatory work is an effective tool to develop and strengthen the local relationships, and its existence is linked to a set of main influences, i.e. Material influences, the need to achieve a personal benefit of a public nature, and Moral influences, which are good-neighborly relations, spatial proximity, the nature of housing and trust in partners.